A volar por los cerros - Medina López, Laura Bibiana (Universidad de San Buenaventura - Cali, 2018)
ith the passage of time, climate change has been a factor that directly affects the environment and within this same highlights the environmental impact on the tutelary hills of the city of Cali. For this reason, we developed this thesis which presents the design of a transmedia project titled A Volar por Los Cerros, which aims to represent and show evidence that the projects carried out by the CVC together with the DAGMA in the tutelary hills of Cali. The object of study for this project will be known as Ecoparque Cerro de la Bandera.This transmedia project consists of an iBook, a web page, a fan page on Facebook and a prototype of a video installation to show the impact of the environmental projects carried out by the respective responsible entities. A research stage is carried out from the purely environmental field and from the field of Multimedia Engineering, aiming to unify knowledge and build a project that has a positive impact on the community. A design of the video-installation involving interactive multimedia technologies is carried out and the prototype of this and the evaluation of the impact caused in the community proceed.